The Initial Process of Dam Construction is Seen from a Topographical Perspective (Bench Mark Coordinates and Control Point Coordinates): Case study of D.I. Bajayu Kab Serdang Bedagai (International Journal of Innovative Research in Computer Science & Technology, 2023)
The research aims to determine the initial  process of dam construction is seen from a topographical  perspective ( bench mark coordinate and control point  coordinates: case study of D.I. Bajayu kab. Serdang Bedagai.  The aim and objective of this topographic survey is to collect  topographical data from the field in order to produce  supporting data in the form of a topographical/situation base  map including cross-sectional and longitudinal cross sectional images along the measurement location. Measurement 20 data of topographi for BM coordinat and  CP coordinat, so: measurements are made up to 50 meters  from the left and right bank of the river, measurement  lengthwise (long section) of ± 8.2 km was carried out from  the confluence of the Padang river with the Bah disappeared  river to the Bajayu free intake location, measurement  benchmark interval for 100 meters straight area and 50  meters turning area,conduct measurements on the linking  route/trace from the planned main building to the free intake  of D.I Bajayu and the first building for D.I Paya Lombang,  measuring 50 meter intervals, the length of the measurement  path from the axle of the weir to the Bajayu free intake is  3,600 m following the embankment to the right of the Padang  river, the length of the canal trace from the axle of the weir  to the building for the first Paya Lombang is 4,600 m  following the existing road.
Keywords: Initial process; Dam contruction; Topographical perspective; Bench mark coordinate; Control point coordinate; case study of D.I. Bajayu kab. Serdang Bedagai